Prognostic values of baseline cortisol levels and neutrophil to lymphocyte ratio in COVID-19 : Prognostic values of baseline cortisol in COVID-19 - Erturk Sengel, Buket; Tukenmez Tigen, Elif; Ilgin, Can; Korten, Volkan; Odabasi, Zekaver (Journal of Medical Biochemistry, 2022)
Background: The prediction of disease severity in COVID-19 is valuable for providing appropriate supportive care earlier and reducing mortality. We aimed to evaluate the impact of baseline cortisol values on disease severity and assess the correlation between the neutrophil to lymphocyte ratio (NLR) and cortisol levels.Methods: In this retrospective study, we compared the prognostic value of baseline the NLR, morning cortisol, ferritin, and C-reactive protein (CRP) levels among patients with severe and nonsevere COVID-19. The relationships were assessed with Spearman’s correlation.Results: Of 167 patients, 63 (37.7%) had severe disease, and their baseline cortisol levels were higher than those in the nonsevere group (18.92 µg/dL vs 13.8 µg/dL, p=0.011). The baseline cortisol level and NLR had area under the curve (AUC) values of 0.62 (95% confidence interval [CI] 0.53-0.71) and 0.70 (CI 95% 0.62-0.78) for the prediction of severe COVID-19, respectively. Severe disease was predicted in patients with a baseline cortisol cutoff ≥ 18.92 µg/dL (552 nmol/L) with a specificity of 75.0%, a sensitivity of 50.79%. The cutoff value for the NLR on day 1 was ≥ 6.2, with a specificity of 93.27% and a sensitivity of 32.79%. Baseline cortisol levels showed a significant weak-moderate positive correlation with the NLR and levels of CRP and ferritin on day 1 (r=0.33, r= 0.29, r= 0.28, respectively, p
Keywords: Cortisol, COVID-19, Neutrophil to lymphocyte ratio, Prediction, Severity